The Relationship Between School Organizational Climate and Teachers’ Organizational Citizenship Behaviors: The Mediating Role of Teaching Efficacy and Moderating Role of Optimistic Traits - Wenmei Sun; Xubo Liu; Yiwen Liu; Sasa Ding; Yan Jiang; Ziyan Lv (Behavioral Sciences)
This study examined the relationship between school organizational climate and teachers’ organizational citizenship behavior, as well as the mediating role of teaching efficacy and the moderating role of optimistic traits. This study was based on social information processing theory, resource conservation theory, and the broaden-and-build theory of positive emotions. We conducted a comprehensive survey of 500 educators from Chinese primary and secondary schools using the Organizational Citizenship Behavior Questionnaire, School Organizational Climate Scale, Sense of Teaching Efficacy Scale, and Optimistic Traits Questionnaire as assessment tools. The results demonstrated that (1) school organizational climate significantly and positively predicted teachers’ organizational citizenship behaviors; (2) teaching efficacy partially mediated the relationship between school organizational climate and teachers’ organizational citizenship behaviors; and (3) optimistic traits moderated the second half of the mediation model in which school organizational climate influenced teachers’ organizational citizenship behaviors through teaching efficacy. Our findings indicated that school organizational climate was an important environmental factor affecting teachers’ organizational citizenship behaviors through their sense of teaching efficacy. Optimistic traits had an important protective effect on teachers’ organizational citizenship behaviors.